Endothelium-derived NO stimulates pressure-dependent renin release in conscious dogs - Persson, Pontus B.; Baumann, J. E.; Ehmke, Heimo; Hackenthal, Eberhard; Kirchheim, Hartmut; Nafz, Benno (American journal of physiology. Renal physiology, 1993)
The effect of blocking the formation of endothelium-derived relaxing factor/nitric oxide (EDNO) on pressure-dependent renin release (RR) was studied in six conscious foxhounds with chronically implanted catheters in the abdominal aorta and the renal vein. Renal blood flow (RBF) was measured with an ultrasonic transit-time flowmeter. RR was determined by multiplying the renal venous-arterial plasma renin activity difference with renal plasma flow. Renal artery pressure (RAP) was reduced in steps by a pneumatic occluder placed around the suprarenal abdominal aorta. A dose of 1,000 mg NG-nitro-L-arginine methyl ester (L-NAME) was given as a bolus to inhibit EDNO formation. In response to L-NAME, RAP increased (98 +/- 3 vs. 128 +/- 3 mmHg; P < 0.05), heart rate decreased (88 +/- 7 vs. 51 +/- 5 beats/min; P < 0.05), RBF decreased (280 +/- 19 vs. 185 +/- 24 ml/min; P < 0.05), and RR decreased (62 +/- 11 vs. 28 +/- 7 U; P < 0.05), whereas glomerular filtration rate changed little (38 +/- 3 vs. 35 +/- 4 ml/min; not significant). Below roughly 90 mmHg, RR was considerably attenuated by L-NAME as RAP was reduced in steps. At the lowest RAP (50 mmHg) RR was 1,946 +/- 406 U during control vs. 697 +/- 179 U after L-NAME (P < 0.05). Thus L-NAME inhibited pressure-dependent RR. This was especially pronounced in the low-pressure range.